LITERATURE REVIEW: APPLICATION OF PROBLEM-BASED LEARNING MODELS TO CHEMISTRY LEARNING OUTCOMES - Saputri, Legendaria Raula; Nisa, Lilis Syahidatul; Rahmawan, Setia (Jurnal Pembelajaran Sains, 2025)
The instructor does not adhere to an effective pedagogical paradigm when presenting the content. One of the reasons why pupils do not study well is because of Guru. Guru does not adopt new methods of instruction and continues to exert control over the class. In light of the outcomes of kimia education, this essay explores using a problem-based learning strategy. This analysis relies on twenty publications in Google Scholar's renting from 2019 to 2023. The data findings utilized in data analysis methods are tables of analyzed articles published in scientific journals. Find academic publications to explore and do descriptive data analysis. The literature study found that using a problem-based learning approach may boost performance in the classroom.